Insurance Client Tracking System - Kalenda Annet Justine (My University, 2024)
ABSTRACT The Insurance Client Tracking System is designed to provide a comprehensive platform for managing insurance clients, policies, and claims. The primary goal of this system is to streamline the process of client registration, policy management, and claims handling, thereby enhancing the efficiency and effectiveness of insurance operations. The system allows clients to easily register for insurance policies, make payments, and submit claims online, while also providing administrators with tools to manage client information, monitor payments, and process claims efficiently. Key features of the system include automated policy renewal reminders, real-time tracking of claim statuses, and comprehensive data management capabilities, ensuring that both clients and administrators can access accurate and up-to-date information at all times. The system is built using robust technologies such as PHP, HTML, MySQL, and JavaScript, which provide a secure and scalable framework for managing large volumes of data and transactions. Additionally, the system includes various security measures to protect sensitive client information and ensure compliance with industry regulations. By automating many of the manual processes involved in insurance management, the Insurance Client Tracking System reduces administrative overhead, minimizes errors, and improves overall client satisfaction. The system also supports risk assessment and compliance tracking, helping insurers identify potential risks and ensure that all regulatory requirements are met.